Patients with Nontuberculous Mycobacterial Lung Disease Exhibit Unique Body and Immune Phenotypes - Kartalija, Marinka; Ovrutsky, Alida R.; Bryan, Courtney L.; Pott, Gregory B.; Fantuzzi, Giamila; Thomas, Jacob; Strand, Matthew J.; Bai, Xiyuan; Ramamoorthy, Preveen; Rothman, Micol S.; Nagabhushanam, Vijaya; McDermott, Michael; et al. (American journal of respiratory and critical care medicine, 2013)
Among patients with nontuberculous mycobacterial lung disease is a subset of previously healthy women with a slender body morphotype, often with scoliosis and/or pectus excavatum. We hypothesize that unidentified factors predispose these individuals to pulmonary nontuberculous mycobacterial disease. To compare body morphotype, serum adipokine levels, and whole-blood cytokine responses of patients with pulmonary nontuberculous mycobacteria (pNTM) with contemporary control subjects who are well matched demographically. We enrolled 103 patients with pNTM and 101 uninfected control subjects of similar demographics. Body mass index and body fat were quantified. All patients with pNTM and a subset of control subjects were evaluated for scoliosis and pectus excavatum. Serum leptin and adiponectin were measured. Specific cytokines important to host-defense against mycobacteria were measured in whole blood before and after stimulation. Patients with pNTM and control subjects were well matched for age, gender, and race. Patients with pNTM had significantly lower body mass index and body fat and were significantly taller than control subjects. Scoliosis and pectus excavatum were significantly more prevalent in patients with pNTM. The normal relationships between the adipokines and body fat were lost in the patients with pNTM, a novel finding. IFN-γ and IL-10 levels were significantly suppressed in stimulated whole blood of patients with pNTM. This is the first study to comprehensively compare body morphotype, adipokines, and cytokine responses between patients with NTM lung disease and demographically matched controls. Our findings suggest a novel, predisposing immunophenotype that should be mechanistically defined.